The design of business : why design thinking is the next competitive advantage - Martin, Roger L. (Boston, Mass : Harvard Business Press, 2009)
Most companies yearn to come up with a game-changing innovation like Apple's iPod, or create an entirely new category like Facebook. Many make genuine efforts to be innovative - they spend on R&D, bring in creative designers, hire innovation consultants. But they get disappointing results. Why? This title offers a provocative answer.
Includes bibliographical references and index
BSBA
Keywords: Creative ability in business; Lateral thinking; Creative thinking; Knowledge management; Management